2017
DOI: 10.1016/j.psychres.2016.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal self-injury and interpersonal violence in U.S. veterans seeking help for posttraumatic stress disorder

Abstract: Nonsuicidal self-injury (NSSI) has been defined as deliberately damaging one's body tissue without conscious suicidal intent. NSSI is a robust predictor of suicidal ideation and attempts in adults. While NSSI has been associated with other-directed violence in adolescent populations, the link between NSSI and interpersonal violence in adults is less clear. The current study examined the cross-sectional relationship between NSSI and past-year interpersonal violence among 729 help-seeking veterans with posttraum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Non-suicidal self-injury (NSSI), defined as the deliberate, self-inflicted damage of any body tissue without suicidal intent and for purposes not socially or culturally sanctioned (International Society for the Study of Self-Injury, 2018), is a strong prospective predictor of suicide attempts (SA) in civilian populations (Asarnow et al ., 2011; Wilkinson et al ., 2011; Hamza et al ., 2012; Ribeiro et al ., 2016). Yet, to our knowledge, only a handful of published studies have investigated the prevalence and characteristics of NSSI in military samples (Klonsky et al ., 2003; Bryan and Bryan, 2014; Kimbrel et al ., 2014; Shelef et al ., 2014; Bryan et al ., 2015 a , 2015 b ; Kimbrel et al ., 2015, 2016, 2017; Calhoun et al ., 2017; Baer et al ., 2018). Like civilian samples, NSSI in military samples is more prevalent in women (Bryan and Bryan, 2014; cf.…”
mentioning
confidence: 99%
“…Non-suicidal self-injury (NSSI), defined as the deliberate, self-inflicted damage of any body tissue without suicidal intent and for purposes not socially or culturally sanctioned (International Society for the Study of Self-Injury, 2018), is a strong prospective predictor of suicide attempts (SA) in civilian populations (Asarnow et al ., 2011; Wilkinson et al ., 2011; Hamza et al ., 2012; Ribeiro et al ., 2016). Yet, to our knowledge, only a handful of published studies have investigated the prevalence and characteristics of NSSI in military samples (Klonsky et al ., 2003; Bryan and Bryan, 2014; Kimbrel et al ., 2014; Shelef et al ., 2014; Bryan et al ., 2015 a , 2015 b ; Kimbrel et al ., 2015, 2016, 2017; Calhoun et al ., 2017; Baer et al ., 2018). Like civilian samples, NSSI in military samples is more prevalent in women (Bryan and Bryan, 2014; cf.…”
mentioning
confidence: 99%
“…Herpertz et al said that NSSIB was closely associated with affect regulation (32). Calhoun et al underlined that the presence of NSSIB was the highest risk for engaging in interpersonal violence (13). Hillbrand et al suggested that repeatedly self-injurious patients were more frequently and more severely aggressive against others, verbally as well as physically (33).…”
Section: Discussionmentioning
confidence: 99%
“…does not assess SDV intent and yielded prevalence rates ranging from 57% to 62% (Calhoun et al, 2017;Kimbrel et al, 2014;Kimbrel, Thomas, et al, 2018). This discrepancy may be due to the treatment-seeking nature of the above samples, yet this remains uncertain given that some prior clinical samples of veterans have documented prevalence estimates as low as 6-14% (Kimbrel et al, 2017;Kimbrel, Meyer, et al, 2018).…”
Section: Aim 1: Describe Clinical and Behavioral Characteristics Ofmentioning
confidence: 99%
“…As one example, research on treatment‐seeking attitudes among active duty service members suggests distinct barriers to disclosing mental health concerns that do not exist for veterans, such as future‐oriented concerns about one's military career (Hom, Stanley, Schneider, & Joiner, 2017). Relatedly, nine of the fourteen studies assessed NSSI in specialized veteran populations, including veterans specifically enrolled in college courses (Blosnich et al, 2015; Bryan & Bryan, 2014; Bryan et al, 2015) or veterans oversampled for PTSD diagnosis (Calhoun et al, 2017; Cunningham et al, 2019; Kimbrel et al, 2015, 2016, 2017) or history of military sexual trauma (MST; Holliday et al, 2018), potentially limiting generalizability to veterans outside these unique diagnostic or environmental circumstances.…”
Section: Introductionmentioning
confidence: 99%